EFFECT OF DICLOFENAС SODIUM ON MECHANISMS OF DIFFERENTIATION OF BONE MARROW CELLS AND PERIPHERAL BLOOD: A LITERATURE REVIEW - Yu. Bahmut; O. S. Ivanov; G. V. Tsapko (Проблеми екології та медицини)
The hematopoietic system is a population of many cells that perform certain functions in the body. The pharmaceutical industry creates new drugs from the group of nonsteroidal anti-inflammatory drugs, but the “gold” standard remains the drug Diclofenac Sodium. In some conditions, a person is forced to take the drug for a long time, and sometimes all life. The mechanism of the drug effect on the bone marrow cells under the condition of long-term administration remains unclear. In the process of analyzing the literature, it has been established that the use of the drug has a toxic effect on the blood cells and blood-forming organs. Gradually, the toxic effect is reduced, but the long-term effect of the drug on the rat organism contributes to the inhibition of the development of erythrocyte and myelocytic sprouts of the bone marrow. A period of up to 10 days is optimal for use, and then it is worthwhile to look for a drug that is safer for the body.